Effect of variable axial load on seismic behaviour of reinforced concrete columns. (1st January 2022) - Wu, Bingyan; Sun, Guangjun; Li, Hongjing; Wang, Shengyu
Highlights: Vertical ground motions cause the axial load to vary at a constant frequency. Variable axial load with large amplitude variation aggravates the damage and asymmetry of the column. Variable axial load with high frequency causes serious damage and negative tangential stiffness of the column. Increasing the phase of variable axial load within 1/4T can reduce its effect on the column. Constraints can change the influence mechanisms of variable axial loads. Abstract: This study investigated the effect of variable axial loads (time-varying axial loads) on the seismic performance and failure mechanism of reinforced concrete (RC) columns with different constraints at the top. The contribution of horizontal and vertical ground motions to the variation in the axial force was revealed by evaluating the axial forces on the RC frame columns and bridge piers under the action of near-fault ground motions. The variation law of the axial force was arrived at using the fast Fourier transform (FFT). Based on previous experiments, 30 cases were designed to discuss the effect of various parameters, namely amplitude, frequency and phase of the variable axial load on the seismic performance of the column. The hysteresis behaviour of specimens under different variable axial loads in terms of hysteresis loops, skeleton curves, stiffness degradations, and energy dissipations were analysed. The results indicated that the frequencies of the variable axial load and lateral displacement of the RC column were constants related to the characteristics of the structure. In addition, variable axial loads were detrimental to the seismic performance of the RC columns, especially those with a large amplitude variation, high frequency, and an identical phase as the lateral drift. It is unsafe to design or evaluate the column based on a constant axial load. Furthermore, constraints at the top of the column strengthened the effect of the variable axial load on the seismic performance of the column, and this resulted in an opposite influence rule of the variable axial load.